Pulsed laser deposition and optical band gap engineering in multinary transparent conducting oxide thinfilms. (March 2015) - Jayaram, P.; Pradyumnan, P.P.; Karazhanov, S.Zh.; Choudary, R.J.; Potty, S.N.
Abstract: Synthesis of ternary and multinary oxide-based films offers the possibility of tuning electrical and optical properties of the existing materials over wide range. Here we report about synthesis and characterization of Zn1.9 Sn0.9 In0.1 Ga0.1 O4, Zn1.9 Sn0.9 In0.2 O4, and Zn1.9 Sn0.9 Ga0.2 O4 grown by a pulsed laser deposition method. These compounds have been synthesized on the base of Zn2 SnO4 by substituting Zn 2+ and Sn 4+ cations with group-III elements such as In 3+ and Ga 3+ . The newly synthesized films are shown to possess a very smooth surface with lower RMS components and exhibit dense grown crystallites with homogenous distribution of small grains. Highly textured growth of inverse cubic spinel structured thinfilms along (111) direction is identified from X-ray diffraction studies. Raman analysis provided supplementary evidences for XRD results. Giant increases of the band gap from 3.60 eV to 3.90 eV have been reported by the development of multinary compounds. The electrical features obtained from Van der Pauw Hall measurements show enhanced charge carrier mobility, resistivity and moderate charge carrier concentrations.